Determination of Arterial Compliance Using Thoracic Bioimpedance to Predict the Presence of Heart Diseases - Souhir Chabchoub; Sofienne Mansouri; Ridha Ben Salah (Publisher: Shahid Beheshti University of Medical Sciences, 2018)
Introduction: Thoracic bioimpedance is a simple, cost-effective, and non-invasive tool used generally to determine several hemodynamic parameters. Based on this technique, the cardiac output and the stroke volume are the most common parameters used for diagnosing heart diseases. This study aims to investigate the ability of the arterial compliance parameter to predict or detect the presence of heart diseases.Methods: two groups of young subjects participated in this study: a control group consisted of 10 subjects including 2 athletes and a group of 10 patients with various heart diseases. The thoracic bioimpedance recordings are used to determine the arterial compliance for the 2 groups of subjects. Statistical analyses are performed using the Student’s t-test and the ROC curve analysis.Results: Experimental results show that the arterial compliance is significantly lower in patients with heart diseases compared to control subjects (P < 0.001).Conclusions: The arterial compliance is a potentially useful hemodynamic parameter which could be successfully used to predict or detect the presence of heart diseases.